Uji Efek Inhibitorik Komponen Bioaktif Bawang Putih (Allium sativum) terhadap Lanosterol 14α-demethylase pada Candida albicans melalui Studi In Silico - Aditya Tri Ananda; Alsya Firdausi Nuzula; Devi Ayu Safitri (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2020)
Candida albicans is a unicellular fungi which causes candidiasis in human and livestock animals especially chicken. Candidiasis could reduce productivity significantly by early culling and causing a great deficit in the farm. Allium sativum or garlic is widely known as herbal which has an inhibitory effect in fungi’s growth. This research’s aim is to prove the effectivity of bioactive compound in Allium sativum to lanosterol 14α-demethylase which plays a role in ergosterol synthesis as a basic structure in fungi’s cell membrane. The ligand sheet retrieved from PubChem database and for the receptor in Protein Data Bank database. Molecular docking conducted by using Autodock Vina and then ligand-receptor complex is visualized with PyMOL and Ligplot+. From compounds that we have been analyzed, Gallic Acid has the most negative binding energy than other compounds have and it has the same amino acid residue with control. In conclusion of that, Gallic Acid in Allium sativum has potential as anti-candidiasis drug.